Does young adult suicide cluster geographically in Scotland?. Issue 8 (13th July 2007) - Exeter, Daniel J; Boyle, Paul J
Abstract : Background: Suicide rose dramatically among young adults in Scotland between 1980–1982 and 1999–2001, especially among those living in deprived areas. Objective: To determine whether there are statistically significant geographical clusters of suicide and undetermined deaths among those aged 15 to 44 years in Scotland, and whether these persist through time. Methods: Deaths from suicide and undetermined causes by young adults in Scotland for three periods—1980 to 1982, 1990 to 1992, and 1999 to 2001—were aggregated into 10 058 small areas for Scotland. Tests for significant (p<0.05) geographical clustering of suicide were carried out for each period separately. Methods of suicide inside the identified clusters were compared with those in the rest of Scotland. Results: A significant geographical cluster of suicide among young adults was identified in east Glasgow in all three time periods (involving 92, 159, and 245 cases). Compared with the rest of Scotland, significantly more deaths in these clusters were caused by poisoning from liquids or solids over the entire period, but this was not the case in the most recent period (1999 to 2001). All three clusters could be explained by the concentration of socioeconomic deprivation in this part of Scotland. Conclusions: One interpretation of this large, persistent, and statistically significant cluster of suicides among young adults in east Glasgow is that suicide is geographically contagious, but the present results suggest that it is explained by the concentration of deprivation in this area. Suicide prevention strategies targeting at-risk populations living in east Glasgow are necessary to reduce the suicide burden in Scotland.